Code-Switching found in Nessie Judge’s Instagram Captions - Sugianitri, Ni Luh Ayu; I Komang Sulatra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
The main goal of this research is to identify the types and to analyze the reasons of code-switching found in Nessie Judge's Instagram captions. This study focuses on the captions where both of Indonesian and English languages are alternated. The study employs both descriptive and qualitative approach. The analysis draws upon Poplack's theory (1980) to classify the types of code-switching present in the data, while Hoffman's theory (1991) is employed to examine the underlying reasons behind these language switch. Both formal and informal method employed in presenting the findings. The analysis reveals 18 data of inter-sentential Code-switching, 13 data of intra-sentential Code-switching, and 7 data of tag switching. The reasons for these Code-switching occurrences are diverse: talking about particular topic 37% of the instances, quoting someone's words 10%, expressing feeling about something accounts for 21%, interjections makes up 21%, repetition used for clarification constitutes 8% and expressing group identity represents 3%.